Helmintofauna monogenética e as táticas reprodutivas da biquara Haemulon plumierii (Lacepède, 1802) - Fernandes, Bruna Laura de França (2017)
Haemulon plumierii are coastal fish that inhabit waters from the Chesapeake Bay - US, Gulf of Mexico, Caribbean and the entire coast of Brazil. Fish are the aquatic vertebrates that have the highest rates of parasitism and use different reproductive tactics in their life strategy to maximize reproduction and ensure the survival of their offspring to adulthood. The present work verified whether the ectoparasitism by monogenetic can influence the reproductive tactics of H. plumierii in marine waters in the North Atlantic Ocean Southwest (4º 50'57 ''S and 37º51'36''O), near the Rio Grande do Norte / Brazil, for that, the parasitic research of monogenetic was carried out and the study of the reproductive tactics of H. Plumierii. 240 copies were captured of H. plumierii hosts in the period from august 2015 to july 2016, with amplitudes of total weight between 84.5 to 517.5g and total length of 175 to 315mm. Monogenetics parasitized 106 H. plumierii fish among 240 examined, and 162 parasites were collected that were distributed in two subclasses: Monopisthocotylea and Polyopisthocotylea. Monopisthocotylea of the family Capsalidae in the genus Encotyllabe (75 in the gills and 9 in the skin) and Entobdella (1 in the gills and 17 in the skin); Polyopisthocotylea in the family Diclidophoridae in the genus Choricotyle (51 in the gills and 9 in the skin). H. plumierii was identified as a new host for the monogenéticos Encotyllabe sp., Entobdella hipoglossi, and Choricotyle sp., being the first record of the genus Entobdella in the family Haemulidae. The monogenetic parasites had a higher parasite preference for the gills, presenting low parasitic ecological indices. It was determined that H. plumierii are seasonal strategist fish in which males present greater total weight, total length and number in relation to females, however, there were no significant differences. It was recorded that the H. plumierii species has the following reproductive tactics: growth of the negative allometric type indicating a greater body increase in length than in weight; independent of this immature (young) stage it was verified macroscopically that adults have three stages of gonadal development (in maturation, mature and emptied) during the reproductive cycle; this animal altered its reproductive strategy, initiating reproductive development with precocity where the absolute fecundity was 52,123 oocytes with a synchronous spawning type in more than two groups; the reproductive period is comprised throughout the year with the highest occurrence in two moments in the months of march to june and the second of august to October. The present work reported that the species Haemulon plumierii is parasitized by monogenetic Monopisthocotylea and Polyopisthocotylea with low prevalence rates, medium intensity and average abundance, and that H. plumierii is a seasonal strategist where his reproductive tactics were not influenced by the parasitism of monogenetics in conditions of low parasitic ecological indices